(untitled) (Argopuro: Jurnal Ilmu Bahasa, 2025)
Abstract This study examines the beauty of meaning created through the use of language styles such as metaphor, personification, and hyperbole in the lyrics of Dewa 19 songs through a stylistic approach. The focus of this study is to recognize and describe the application of these figures of speech and evaluate their contribution to the meaning and aesthetic value of the lyrics. The approach used is qualitative descriptive analysis by highlighting the aspects of language and language style used. The findings of the study show that metaphors provide images used to convey messages poetically by replacing the original meaning with figurative meaning, personification gives life to inanimate objects or abstract concepts so that the lyrics feel more alive and touching, and hyperbole presents an exaggerated image to emphasize feelings dramatically. This study applies the library technique of listening and noting by reading all the song lyrics thoroughly, then continuing by noting all the figures of speech found during the analysis process. The results of this study reveal that metaphors are more dominant than personification and hyperbole. Keywords: style of language, song lyrics, stylistics Abstrak Penelitian ini mengkaji keindahan makna yang tercipta melalui penggunaan gaya bahasa seperti metafora, personifikasi, dan hiperbola dalam lirik lagu dari Dewa 19 melalui pendekatan stilistika. Fokus penelitian ini adalah mengenali dan menguraikan penerapan majas-majas tersebut serta mengevaluasi kontribusinya terhadap makna dan nilai estetika lirik. Pendekatan yang dipakai adalah analisis kualitatif deskripsi dengan menyoroti aspek bahasa dan gaya bahasa yang digunakan. Temuan penelitian memperlihatkan bahwa metafora memberikan gambaran digunakan untuk menyampaikan pesan secara puitis dengan menggantikan makna asli menjadi makna kiasan, personifikasi memberikan kehidupan pada objek benda mati atau konsep abstrak sehingga lirik terasa lebih hidup dan menyentuh, dan hiperbola menghadirkan gambaran yang secara berlebihan untuk menegaskan perasaan secara dramatis. Penelitian ini menerapkan teknik pustaka simak dan catat dengan cara membaca secara menyeluruh seluruh lirik lagu, kemudian melanjutkan dengan mencatat semua majas yang ditemukan selama proses analisis. Hasil dari penelitian ini mengungkapkan bahwa majas metafora lebih dominan muncul dibandingkan dengan majas personifikasi dan hipérbola. Kata kunci : gaya bahasa, lirik lagu, stilistika